DETERMINANTS OF ENTREPRENEURSHIP DEVELOPMENT IN THE OPINION OF THE AUTHORITIES OF RURAL AND SEMI-URBAN MUNICIPALITIES IN WARMIŃSKO-MAZURSKIE VOIVODESHIP - Pomianek, Iwona (Acta Scientiarum Polonorum. Oeconomia, 2018)
The paper presents opinions of local government authorities on determinants of local entrepreneurship development. The research conducted in 2017 in rural and urban-rural municipalities of Warmińsko-Mazurskie Voivodship (Poland) shows that among the locational conditions for entrepreneurship development the tourist attractiveness was rated as the highest. Infrastructural conditions were assessed as favourable while such features of the residents as education level, age or qualifications were satisfactory for the respondents. Protected natural areas, popular in the analysed region, were both a barrier and an opportunity for entrepreneurship development. Moreover, self-government activities were evaluated as good on the local level, and satisfactory on the regional level.